2016
DOI: 10.1590/1806-9061-2015-0011
|View full text |Cite
|
Sign up to set email alerts
|

Requirement of Digestible Sulfur Amino Acids in Laying Hens Fed Sorghum- and Soybean Meal-Based Diets

Abstract: Two experiments were done to evaluate the effect of increasing levels of dietary digestible methionine (Met) and Met:cysteine (Met:Cys) ratio on the productivity of Hy-Line W-36 laying hens fed sorghum-and soybean meal-based diets. In Exp. 1, 160 hens from 68 to 75 weeks of age were assigned to four dietary levels of digestible Met (0.20 0.24, 0.28 and 0.32%). The digestible total sulfur amino acids:Lysine (TSAA:Lys) ratios were: 62, 68, 76 and 84%. In Exp. 2, 192 hens from 76-83 weeks of age were assigned to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…A similar observation was also made by Gomez and Angeles. 39 Increasing the concentrations of TSAA to an optimum level was able to compensate only 50% of the decrease in EP or FCR or FE, whereas EW could not be improved with TSAA supplementation and, hence, mechanisms other than a reduced availability of these amino acids might be involved in the inhibitory effect of GM on EP, EW or FCR in laying chickens. Although concentrations of Ile and Val were lower than the recommended levels in the groups fed GM, the group with TSAA 6.84 g kg −1 within the GM cluster had concentrations of Ile and Val nearer to the recommended levels, although this group had a much lower EP than the control group (without GM) containing a similar level (6.84 g kg −1 ) of TSAA.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…A similar observation was also made by Gomez and Angeles. 39 Increasing the concentrations of TSAA to an optimum level was able to compensate only 50% of the decrease in EP or FCR or FE, whereas EW could not be improved with TSAA supplementation and, hence, mechanisms other than a reduced availability of these amino acids might be involved in the inhibitory effect of GM on EP, EW or FCR in laying chickens. Although concentrations of Ile and Val were lower than the recommended levels in the groups fed GM, the group with TSAA 6.84 g kg −1 within the GM cluster had concentrations of Ile and Val nearer to the recommended levels, although this group had a much lower EP than the control group (without GM) containing a similar level (6.84 g kg −1 ) of TSAA.…”
Section: Discussionmentioning
confidence: 93%
“…Although data on the effect of GM inclusion on amino acid requirement could not be traced, studies conducted by Rhone‐Poulenc showed that, if tannin from sorghum is higher than 5.0 g kg −1 in the diet, amino acid digestibility is reduced, which may alter requirements. A similar observation was also made by Gomez and Angeles …”
Section: Discussionmentioning
confidence: 99%
“…In the study of Gomez and Angeles (2016) the effect of the ratio of digestible MET : digestible CYS at a constant digestible M+C concentration (0.52%) was investigated. The digestible MET and CYS levels both varied from 0.20 -0.32%.…”
Section: Sid-met Requirementmentioning
confidence: 99%
“…14). and egg mass (g/d/hen) based on the data of Gomez and Angeles (2016). Using the quadratic broken-line model as described in the M&M section of this document optimal dig.…”
Section: Sid-met Requirementmentioning
confidence: 99%
See 1 more Smart Citation